Les lieux d’origine du devoir de mémoire - Sébastien Ledoux (Conserveries Mémorielles)
This text examines the as-of-yet unfinished trajectory of the French expression “devoir de mémoire” (“duty to remember”), focusing primarily on the beginnings of its use. Questions surrounding its starting point have produced a certain amount of scientific literature centered on the origins of the term, which it associates with the testimony of concentration camp survivors. This association was furthered by a discursive memory of the term which, during the 1990s, primarily designated things referring to the memory of the Holocaust. This historicization undertakes to reconstitute the trajectory of the “devoir de mémoire,” focusing on roots rather than origins. It explores the first, disparate usages of the term and its various incarnations over the course of the 1970s. The creation of this figure of speech is rooted in the new discursive constructions centering on “memory” during the 1970s and the 1980s, a time of important historical methodological changes. The new practices fostered a historiographic renewal for a new generation of historians who contributed to the understanding, through language is used, of this question, raised at the same moment of our “regime of historicity.”